Four Polymorphs of Methyl Paraben: Structural Relationships and Relative Energy Differences - Gelbrich, Thomas (American Chemical Society, 2013)
[Image: see text] Four polymorphic forms of methyl paraben (methyl 4-hydroxybenzoate, 1), denoted 1-I (melting point 126 °C), 1-III (109 °C), 1-107 (107 °C), and 1-112 (112 °C), have been investigated by thermomicroscopy, infrared spectroscopy, and X-ray crystallography. The crystal structures of the metastable forms 1-III, 1-107, and 1-112 have been determined. All polymorphs contain the same O–H···O=C connected catemer motif, but the geometry of the resulting H-bonded chain is different in each form. The Z′ = 3 structure of 1-I (stable form; space group Cc) contains local symmetry elements. The crystal packing of each of the four known crystal structures of 1 was compared with the crystal structures of 12 chemical analogues. Close two-dimensional relationships exist between 1-112 and a form of methyl 4-aminobenzoate and between 1-107 and dimethyl terephthalate. The lattice energies of the four methyl paraben structures have been calculated with a range of methods based on ab initio electronic calculations on either the crystal or single molecule. This shows that the differences in the induction energy of the different hydrogen-bonded chain geometries have a significant effect on relative lattice energies, but that conformational energy, repulsion, dispersion, and electrostatic also contribute.